Structural analysis and blood-enriching effects comparison based on biological potency of Angelica sinensis polysaccharides - Tian, Yunxia; Shen, Xiaorui; Hu, Tingting; Liang, Ziyu; Ding, Yu; Dai, Huilian; Liu, Xinyuan; Lu, Tulin; Yin, Fangzhou; Shu, Yachun; Guo, Zhijun; Su, Lianlin; et al. (Frontiers in Pharmacology, 2024)
Angelica sinensis is a long-standing medicine used by Chinese medical practitioners and well-known for its blood blood-tonic and blood-activating effects. Ferulic acid, ligustilide, and eugenol in Angelica sinensis activate the blood circulationblood; however, the material basis of their blood-tonic effects needs to be further investigated. In this study, five homogeneous Angelica sinensis polysaccharides were isolated, and their sugar content, molecular weight, monosaccharide composition, and infrared characteristics determined. Acetylphenylhydrazine (APH) and cyclophosphamide (CTX) were used as inducers to establish a blood deficiency model in mice, and organ indices, haematological and biochemical parameters were measured in mice. Results of in vivo hematopoietic activity showed that Angelica sinensis polysaccharide (APS) could elevate erythropoietin (EPO), granulocyte colonystimulating factor (G-CSF), and interleukin-3 (IL-3) serum levels, reduce tumor necrosis factor-α (TNF-α) level in mice, and promote hematopoiesis in the body by regulating cytokines levels. Biological potency test results of the in vitro blood supplementation indicated strongest tonic activity for APS-H2O, and APS-0.4 has the weakest haemopoietic activity. The structures of APS-H2O and APS-0.4 were characterisedcharacterized, and the results showed that APS-H2O is an arabinogalactan glycan with a main chain consisting of α-1,3,5-Ara(f), α-1,5-Ara(f), β-1,4-Gal(p), and β-1,4-Gal(p)A, and two branched chains of β-t-Gal(p) and α-t-Glc(p) connected to each other in a (1→3) linkage to α-1,3,5-Ara(f) on the main chain. APS-0.4 is an acidic polysaccharide with galacturonic acid as the main chain, consisting of α-1,4-GalA, α-1,2-GalA, α-1,4-Gal, and β-1,4-Rha. In conclusion, APS-H2O can be used as a potential drug for blood replenishment in patients with blood deficiency, providing a basis for APSs application in clinical treatment and health foods, as well as research and development of new polysaccharide-based drugs.